AB0575 Age is an Independent Risk Factor for Thrombosis in Antiphospholipid Antibody Carriers. (9th June 2015) - Les, I.; Vidal, C.; Anaut, P.; Sánchez, C.; Andía, A.
Abstract : Background: Unlike antiphospholipid antibody (aPL) profile or arterial hypertension and hypercholesterolemia, age has not been identified as a risk factor for thrombosis by previous scores and studies on antiphospholipid syndrome (APS). 1-3 However, age increases the thrombotic risk of patients in other settings (i.e. atrial fibrillation). 4 Objectives: To investigate the impact of multiple factors including the age on the risk of thrombosis in aPL carriers. Methods: Retrospective study of a historical cohort of patients with medium-high titres of aPL according to current recommendations on APS, recruited in the outpatient clinic of a tertiary care hospital. Association between occurrence of thrombosis and several variables such as age, gender, arterial hypertension, hypercholesterolemia, diabetes mellitus, tobacco use, oral contraceptive therapy, mean platelet volume, lupus anticoagulant (LA), anticardiolipin antibodies (aCL), anti-β2-glycoprotein I antibodies, APS score and Global APS score was assessed by univariate analysis followed by multivariate logistic regression. Diagnostic accuracy of the independent variables was evaluated by receiver operating characteristic (ROC) curve analysis. Results: Fifty patients (38 women, 12 men; baseline age 49±18 years), of which 27 fulfilled definite classification criteria for APS (18 primary APS, 9 secondary APS), were followed for 4.95±5.48 years. At baseline, 26 patients had ≥1 cardiovascular risk factors (15 tobacco use, 13 arterial hypertension, 8 hypercholesterolemia and 4 diabetes mellitus). Twenty-three patients developed 27 thrombotic events (14 in venous bed, 13 in arterial bed) including 4 thrombotic recurrences. Compared with patients without thrombosis, patients with thrombosis were older (57±18 vs 42±14 years, p<0.01), had more frequently ≥1 cardiovascular risk factors (17/23 vs 9/27, p<0.01) and were more frequently positive to LA+aCL (9/23 vs 4/27, p=0.05). The logistic regression model confirmed the age (OR=1.05, 95%CI=1.01-1.10, p=0.02), the cardiovascular risk factors (OR=4.61, 95%CI=1.10-19.32, p=0.03) and the double positivity to LA+aCL (OR=7.71, 95%CI=1.19-49.80, p=0.03) as independent predictors of thrombosis. For this set of three variables, the area under the ROC value was 0.85 (graph). Conclusions: As with traditional cardiovascular risk factors and coexistence of LA+aCL, advanced age is also associated with a higher risk of thrombosis in aPL carriers. The type and intensity of thromboprophylaxis should be based on a thorough risk-benefit balance, especially in the elderly patients. References: Ruffati A, Del Ross T, Ciprian M, et al. Risk factors for a first thrombotic event in antiphospholipid antibody carriers: a prospective multicentre follow-up study. Ann Rheum Dis 2011;70:1083-6. Otomo K, Atsumi T, Amengual O, et al. Efficacy of the antiphospholipid score for the diagnosis of antiphospholipid syndrome and its predictive value for thrombotic events. Arthritis Rheum 2012;64:504-12. Sciascia S, Sanna G, Murru V, et al. GAPSS: the Global Anti-Phospholipid Syndrome Score. Rheumatology 2013;52:1397-403. Lip GY, Nieuwlaat R, Pisters R, Lane DA, Crijns HJ. Refining clinical risk stratification for predicting stroke and thromboembolism in atrial fibrillation using a novel risk factor-based approach: the euro heart survey on atrial fibrillation retrieved no results. Chest 2010;137:263-72. Disclosure of Interest: None declared